Dashboard BI untuk Visualisasi Harga Bahan Pokok Provinsi Jawa Barat - Setiawan, Dany; Trisnawarman, Dedi; Perdana, Novario Jaya (Jurnal Sains dan Teknologi (JSIT), 2025)
This study aims to design and implement an interactive Business Intelligence (BI)-based dashboard to visualize staple food price data in West Java Province. The data were obtained from the National Strategic Food Price Information Center (PIHPS)–Bank Indonesia, covering the period from January 2023 to December 2024. The Extract, Transform, Load (ETL) process was carried out using Power Query, and the processed data were stored in a MySQL database using a star schema model consisting of fact and dimension tables. Data visualization was developed using Power BI, featuring key indicators such as average price, highest price, lowest price, previous month’s average price, and 3- and 6-month moving averages. The dashboard provides interactive filtering features based on time period, region, and commodity type. The results of Black Box Testing indicate that all system functions operate as expected. This dashboard is expected to enhance price information transparency and support data-driven decision-making for government agencies, business actors, and the public.Key words